CD8 T cell dynamics and immune cell trafficking in ZIKV infection: implications for neuroinflammation and therapy - Sungjun Park (Virology Journal)
Abstract The 2015–2016 Zika virus (ZIKV) epidemic underscored the severe consequences of congenital Zika syndrome (CZS) and the broader challenges posed by neurotropic flaviviruses. As key mediators of cytotoxic immunity, CD8 T cells play a crucial and multifaceted role in ZIKV pathogenesis. While essential for controlling viral replication, their infiltration into the central nervous system (CNS)—an immune-privileged site—raises potential concerns regarding immunopathology. This review explores the dual roles of CD8 T cells during ZIKV infection, emphasizing both their antiviral functions and their potential to drive neuroinflammation. We examine how ZIKV infection and chemokine-mediated signals facilitate immune cell trafficking across the blood–brain barrier, drawing parallels with other neurotropic flaviviruses. We also explore how therapeutic agents, such as the S1P receptor modulator FTY720, influence lymphocyte trafficking and CNS immune regulation. Finally, we review emerging interventions—including vaccines, antivirals, immunomodulators, and passive immunotherapies—that aim to achieve effective viral control while minimizing neural damage. A balanced understanding of immune cell responses in flavivirus infections is essential for guiding future therapeutic strategies against ZIKV and related neurotropic viruses.